ANALYSIS OF INVESTOR LOYALTY ON STOCK BROKERAGE COMPANIES: EMPIRICAL EVIDENCE IN INDIVIDUAL STOCK INVESTORS IN ACEH PROVINCE - Thasrif Murhadi; Desi Purnamasari; Suhad (CV. Radja Publika, 2023)
This study aims to examine the effect of e-service quality, brand image and trust on investor satisfaction as well as its impact on stock investor loyalty in Aceh Province. A structured questionnaire was used to collect data from investors who have stock accounts in securities companies operating in Aceh. Validity and reliability tests used SPSS. This research model test used SEM Amos. The results of data analysis found that there was a positive and significant effect of service quality, brand image and trust on investor satisfaction. There was a positive and significant effect of investor satisfaction on investor loyalty, and there was a positive and significant effect of e-service quality and brand image on investor loyalty. Trust did not affect positively and significantly to investor loyalty. The trust effect on loyalty, however, was greater through the mediation variable. More variation in results could be obtained through a wider range of respondents. Other factors such as descriptive norms and perceived usefulness should be used to increase the explanatory power of the dependent variable. The comparison of the similar study on explanatory power between other customer behavior-based models could make another valuable contribution. This study would provide information on the factors affecting investor loyalty to stock brokerage companies. Moreover, the results of this study could serve as a guideline for stock brokerage companies in understanding the factors and programs that needed to embed to increase retail stock investor loyalty. Not many studies have examined the behavior of retail investors in Indonesia, particularly in Aceh Province.